2020
DOI: 10.4236/aim.2020.1010040
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Biosurfactant Production by <i>Pseudomonas aeruginosa</i> Strain CGA1 Using Agro-Industrial Waste as Sole Carbon Source

Abstract: Biosurfactants are biomolecules produced by microorganisms, which possess several advantages over their chemical counterparts. Production can be cost-effective if renewable wastes are utilized as substrates. In this study, optimization of biosurfactant production by Pseudomonas aeruginosa strain CGA1 was carried out using response surface methodology. The conventional "One factor at a time" method of optimization was initially adopted to ascertain the impact of different renewable wastes on biosurfactant produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The production of biosurfactants is highly dependent upon the type and quantity of ingredients present in the culture media. Selecting the right sources of nitrogen and carbon or other nutrients is major step in designing a productive and cost-effective biosurfactant production process ( 45 ). For instance, ( 41 ) reported the rice bran hydrolysate as the only substrate between different agricultural by-products for biosurfactant production by L. plantarum PTCC 1896 resulting in a significant emulsification activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The production of biosurfactants is highly dependent upon the type and quantity of ingredients present in the culture media. Selecting the right sources of nitrogen and carbon or other nutrients is major step in designing a productive and cost-effective biosurfactant production process ( 45 ). For instance, ( 41 ) reported the rice bran hydrolysate as the only substrate between different agricultural by-products for biosurfactant production by L. plantarum PTCC 1896 resulting in a significant emulsification activity.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Ghasemi et al ( 18 ) was attained a significant surface tension reduction (41.97 %) from L. rhamnosus by using low-quality date syrup ( 18 ). The high biosurfactant production with sugar cane molasses and whey permeate is attributed to the presence of valuable sugar, protein, minerals, vitamins, and organic acids for the fermentation process ( 45 , 46 ). To our knowledge, few studies were conducted using whey permeate and sugar cane molasses used as the source of carbon for the production of biosurfactant from L. plantarum .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was found that the most effective medium for pyocyanin production by Pseudomonas aeruginosa was nutrient broth supplemented with maltose. A Central Composite Design (CCD) of RSM to optimize key media components for enhanced pyocyanin yield was carried out [14]. A 2 4 -full factorial central composite design was employed to establish a second-order polynomial model.…”
Section: Optimization Of Pyocyanin Production Using the Response Surf...mentioning
confidence: 99%
“…The R 2 value measures the percentage of variance that the considered model can explain. The best conditions were confirmed and recorded as the mean±SD [15]. The response optimizer of Minitab version 17 was used to predict the optimum conditions for pyocyanin production by P. aeruginosa.…”
Section: Empirical Validation Of the Statistical Modelmentioning
confidence: 99%
“…Biosurfactants are amphiphilic substances with hydrophobic and hydrophilic parts (1,21). Surface-active molecules are synthesized commonly by bacteria, yeast, and fungi (5,13). The biological surfactants are safe, biodegradable, have good surface activity, high specificity, and are effective in stressful environments, making them eco-friendly (23,43).…”
Section: Introductionmentioning
confidence: 99%